2022
DOI: 10.3889/oamjms.2022.9385
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with a Health-promoting Lifestyle among Adults and Older Adults in the Era of COVID-19: An Integrative Review

Abstract: AIM: To identify the factors associated with a health-promoting lifestyle (HPL) among adults or older adults during the COVID-19 pandemic. METHODS: On the basis of the PRISMA guidelines, primary articles published in English within the period from December 2019 to December 2021 were searched for on five databases: PubMed, Cochrane Library, Scopus, Web of Science, and CINAHL Plus with Full Text. RESULTS: The current review identified nine relevant studies with a total of 4,509 adults and older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Maintaining physical and mental well-being throughout life and into old age, SN contributes to HPBs and quality of life [ 43 ]. A recent integrative review of factors associated with HPBs during the COVID-19 pandemic revealed that more social engagement with SNs was associated with HPBs among older adults [ 44 ]. These findings have been supported with a prior SEM study that examined the factors affecting HPBs among older women in Korea [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining physical and mental well-being throughout life and into old age, SN contributes to HPBs and quality of life [ 43 ]. A recent integrative review of factors associated with HPBs during the COVID-19 pandemic revealed that more social engagement with SNs was associated with HPBs among older adults [ 44 ]. These findings have been supported with a prior SEM study that examined the factors affecting HPBs among older women in Korea [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive feedback from the residents emphasized the significance of accessible and efficient healthcare services in ensuring the well-being of the population. According to Suksatan et al (2022), the concept of health promotion suggests that individuals' adoption of behaviors that promote their health is influenced by the cognitive and emotional factors related to those behaviors. These factors interacted with their personal characteristics and past experiences.…”
Section: -Impact Of Covid-mentioning
confidence: 99%
“…Additionally, elderly individuals are more likely to suffer from chronic underlying diseases, making them more prone to infection; therefore, mortality and serious complications are more common among seniors, especially those with chronic illnesses (3). Specifically, health conditions such as high blood pressure, diabetes, and coronary and cerebral vascular diseases can increase the risk of severe complications from the coronavirus in older adults (2).…”
Section: Introductionmentioning
confidence: 99%
“…A health-promoting lifestyle is a sub-pattern of appropriate behaviors (such as eating healthy, engaging in physical activity, sleeping well), along with avoiding unhealthy food, alcohol, and smoking, which can improve an individual's health and well-being (3). According to Walker (1990), a health-promoting lifestyle is "a multidimensional pattern of perceptions and actions initiated by the individual, aimed at continuing and enhancing their level of health and self-actualization."…”
Section: Introductionmentioning
confidence: 99%